GFAP alternative splicing regulates glioma cell–ECM interaction in a DUSP4‐dependent manner. Issue 11 (31st August 2019) - van Bodegraven, Emma J.; van Asperen, Jessy V.; Sluijs, Jacqueline A.; van Deursen, Coen B. J.; van Strien, Miriam E.; Stassen, Oscar M. J. A.; Robe, Pierre A. J.; Hol, Elly M.
Abstract : Gliomas are the most common primary brain tumors. Their highly invasive character and the heterogeneity of active oncogenic pathways within single tumors complicate the development of curative therapies and cause poor patient prognosis. Glioma cells express the intermediate filament protein glial fibrillary acidic protein (GFAP), and the level of its alternative splice variant GFAP‐δ, relative to its canonical splice variant GFAP‐α, is higher in grade IV compared with lower‐grade and lower malignant glioma. In this study we show that a high GFAP‐δ/α ratio induces the expression of the dual‐specificity phosphatase 4 (DUSP4) in focal adhesions. By focusing on pathways up‐ and downstream of DUSP4 that are involved in the cell‐extracellular matrix interaction, we show that a high GFAP‐δ/α ratio equips glioma cells to better invade the brain. This study supports the hypothesis that glioma cells with a high GFAP‐δ/α ratio are highly invasive and more malignant cells, thus making GFAP alternative splicing a potential therapeutic target.—Van Bodegraven, E. J., van Asperen, J. V., Sluijs, J. A., van Deursen, C. B. J., van Strien, M. E., Stassen, O. M. J. A., Robe, P. A. J., Hol, E. M. GFAP alternative splicing regulates glioma cell–ECM interaction in a DUSP4‐dependent manner. FASEB J. 33, 12941–12959 (2019). www.fasebj.org